CORPORATE SOCIAL RESPONSIBILITY (CSR): A NEW PARADIGM OF ACCOUNTING FOR ENVIRONMETALLY BASED COMPANIES - Yuni Ekawarti; Maya Dini; Desfitrina Desfitrina; Subiyanto Subiyanto; Zulfadhli Zulfadhli (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2023)
The response of a corporation to a crisis must be based on the inclusion of social value creation in its mission, which goes beyond generating economic value for shareholders. However, corporate social responsibility (CSR) is not about how benefits are shared but about how they are created; as a result, CSR should be viewed as a new accounting and management model, rather than as a marketing tool, to be effective. Integration of CSR concepts and ideas at all levels of a business is required to implement CSR successfully. As a result, companies that successful align their stakeholders and implement responsible environmental accounting will achieve a competitive advantage that is difficult to imitate. This article aims to explore the concept of CSR and its dimensions, in dialogue with stakeholders, across various management instruments in terms of corporate responsibility and its strategic value; in such a way that companies that are successful in alligning their stakeholders and implementing responsible environmental accounting will achieve a competitive advantage that is difficult to imitate . The limitation of this research is that it is only in the form of descriptive analysis, so it cannot describe how it is implemented directly in business entities.